Exploring Students’ Motivation to Learn and Efforts to Develop It: A Case Study at a Quranic Educational Institution - Puspita, Della; Idris, Muhammad; Setiawan, Edi; Juniarti, Elgin; Gustiana, Else (El-Rusyd, 2026)
Learning motivation plays a crucial role in supporting the success of learning activities at Quranic education institutions. Observations in the field indicate variations in learning motivation, with some students at these institutions still exhibiting less-than-optimal enthusiasm. This study aims to explore the actual state of learning motivation, identify determining factors, and map out and formulate strategies for its development in a thorough and detailed manner. A qualitative approach using a case study design was employed, focusing on an in-depth analysis of a single institutional setting as the unit of analysis. Data collection was conducted through participant observation, in-depth interviews, and documentation involving teachers, students, and parents. The research findings indicate that motivation is the result of an interaction between internal factors including interest, self-confidence, and physical condition and external factors such as family support, teaching methods, peer influence, and excessive use of electronic devices. Based on these findings, integrated development strategies have been identified and formulated, including creative and interactive learning, strengthening partnerships with parents, a reward system, and the development of a sustainable religious education program. In conclusion, this case study demonstrates that improving motivation requires an approach tailored to the unique characteristics and needs of the Quran educational institution in question.